Letramento em saúde: associação com dados sociodemográficos, autopercepção da saúde e qualidade de vida em adultos usuários da atenção primária à saúde - Suzana Raquel Lopes Marques (2016)
Introduction: To know the health literacy of individuals and populations can foster the achievement of better health outcomes. Thus, it is important to consider the health literacy assessment tools available, its potential and limitations. It is also important to be aware of the association between health literacy and factors that influence it to abroader understanding of the subject and planning of interventions that promote health and quality of life. Purpose: To investigate health literacy and its association with sociodemographic factors, self-perceived health and quality of life in adults, users of the primary health care in a city of the Metropolitan Region of Belo Horizonte, Minas Gerais. Methods: The first stage of the study was a systematic review of the literature on health literacy assessment tools, in the search platforms PubMed (US NationalLibrary of Medicine), Web of Science and BVS - Lilacs (Virtual Health Library - Latin American and Caribbean Literature in Health Sciences). The Medical Subject Headings (MeSH), DeCS (Descriptors in Health Sciences) and the free term "literacy" were combined by Boolean operators AND and OR. The review included articles published from 2009 to 2014, in Portuguese, English or Spanish, which used tools forassessment of general and specific health literacy that would allow to assess health literacy in general. Titles and abstracts were read, followed by the full reading of the articles that met the selection and analysis criteria through a structured protocol (according to recommendations of the initiative Strengthening the Reporting ofObservational studies in Epidemiology - STROBE). This process was performed by two reviewers, being 27 articles selected for review. The second stage dealt with observational analytic cross-sectional study with adults aged between 20 and 59 years, men and women, users of the primary health care of the municipality of the Metropolitan Region of Belo Horizonte. The sample was probabilistic, stratified according to the Basic Health Units (UBS) of reference, gender and age, and consistedof 380 individuals. The data were collected in the UBS from February to May 2015. The following research tools were applied individually through interviews: Short Assessment of Health Literacy for Portuguese-speaking Adults (SAHLPA-18) for assessment of the health literacy response variable; Sociodemographic Questionnaire and Brazilian Economic Classification Criterion (BECC) for assessment of the sociodemographic factors; Questionnaire of self-perceived health to investigate selfperceived health and World Health Organization Quality of Life (WHOQOL) for assessment of the quality of life. A descriptive analysis of the data was carried out by frequency distribution, measures of central tendency and dispersion. A bivariate analysis was performed through Mann-Whitney or Persons Chi Square tests. Variables with statistically significant associations at the level of 20% (p<0.20) in the bivariate analysis were considered for inclusion in the multiple logistic regressionmodel. Variables with significant association at the level of 5% (p<0.05) were kept in the final model. The magnitude of the associations was assessed by Odds Ratio (OR) and its respective confidence intervals at 95%. Another stage of the field research was the proposal of an instrument for assessment of the perception of health literacy inadults, the Health Literacy Scale (ELS). The ELS, structured in functional and communicative axles, the SAHLPA-18 and the Sociodemographic Questionnaire were used for this study. Descriptive analyses, internal consistency, confirmatory factor analysis and convergent validity (Spearman correlation) were performed. Results: In the 27 articles analyzed in the review, 36 health literacy assessment tools wereidentified, being 17 distinct types. The Test of Functional Health Literacy in Adults (TOFHLA) and the Rapid Estimate of Adult Literacy in Medicine (REALM) were the most commonly used instruments (29,6%, n=8 articles each). The use of tools for assessment of general and specific health literacy occurred in 14 articles (51.9%). Most studies had a cross-sectional observational design (81.5%), conducted in NorthAmerica (48.1%) and Europe (22.2%), in outpatient clinics or hospitals (63.0%). The findings of the field research indicated that inadequate health literacy was frequent (74.5%) and, in the bivariate analysis, it was associated with gender, schooling, last grade concluded, minimum formal study, BECC, health insurance, family arrangement, importance attributed to health, own health assessment, UBS attendance rate and with the domains of social and environmental relations of the WHOQOL. In the final model of logistic regression analysis, only the variable schooling remained associated with health literacy (p<0.001), being that individuals with primary and secondary education presented, respectively, 22.1 and 4.2 times the chance to have inappropriate health literacy compared to those with higher schooling. In the psychometric analysis of the ELS, it was found that most participants of the research have completed or partially attended high school (44.8%) and deny difficulties in relation to health literacy in the situations presented in the ELS. The internal consistency of the scale presented a reliability considered acceptable to good after the removal of question 5 (=0,763). Theconfirmatory factor analysis confirmed the option of extraction of a single item from the ELS, so that the final structure of the instrument was of nine items. The correlation analysis between ELS and SAHLPA-18 as well as between ELS and schooling was significant (p<0,001) but considered weak (respectively r=0.369 e r=0.305). Conclusion: There are various tools for the assessment of health literacy. The predominance of the use of TOFHLA and REALM clinical screening tests was observed, with focus on functional health literacy. It was found that inadequate healthliteracy was frequent and it showed a positive association only with schooling, so that individuals with less schooling were more likely to have inadequate health literacy. The ELS showed the most appropriate conformation when composed of nine items. The correlation between ELS and the SAHLPA-18 instrument and between ELS and schooling was weak, although statistically significant.